Incorporating Chatgpt In The Academic Research Process: Avoiding Student Stigmatization - El-Sakran, Tharwat M. (2024)
ChatGPT, a potent and readily accessible technological tool, has recently raised concerns regarding its potential for fostering plagiarism within educational contexts. With its emergence, academic institutions have begun disseminating cautionary advisories to educators, urging them to incorporate notifications in their syllabi to apprise students that the utilization of this application could impinge upon their academic integrity, potentially resulting in a failing grade for their submitted work. While these apprehensions possess a certain degree of validity, university professors had anticipated that their institutions would furnish them with comprehensive training sessions on the utilization of ChatGPT and its pertinent functionalities for pedagogical purposes. The primary objective of this research is to introduce ChatGPT and elucidate how it can be harnessed to encourage tertiary-level students in the composition and refinement of their academic research papers, thereby aiding them in attaining the prescribed learning outcomes delineated in their respective syllabi and the guidelines governing academic writing courses. Furthermore, rather than resorting to punitive measures and undue stress imposition, educational institutions should endeavor to evince genuine concern for their students' well-being. The author posits that the extent of plagiarism facilitated by ChatGPT is contingent upon the nature of the course in which it is employed. Consequently, course instructors should consider implementing tailored instructional and assessment strategies, which will be expounded upon in this study. The research culminates by offering recommendations for the preservation of students' well-being and the mitigation of distrust.